Efeito do Carvacrol em ratos com hipertensão pulmonar Induzida por Monocrotalina - Alves, Rayanne Maira Felix Ribeiro (2019)
Pulmonary hypertension (PH) is characterized by an increase in pulmonary vascular tone, which leads to elevated pulmonary artery pressure, right ventricular failure and death. The carvacrol (CRV) is a phenolic monoterpene present in some aromatic plants, and its contain important properties such as vasorelaxant, anti-inflammatory, antibacterial and anti-tumor activity. The aim of this study was to evaluate the effects of carvacrol in treatment monocrotaline (MCT)-induced PH in rats. For the development of this study, male Wistar rats were injected subcutaneously with saline 0,9% (control group - CTL) or monocrotaline (60mg/Kg) to develop PH. They were divided into the following groups: CTL; MCT; MCT+CRV 50mg/Kg; MCT+CRV 100mg/Kg; and MCT+SILD (sildenafil 50mg/Kg). 24 hours later, rats were treated daily with oral administration for 28 days. The following parameters were evaluated: pulmonary artery pressure (PAP), right ventricular weight to left ventricular plus septum weight ratio (Fulton index), vascular reactivity, pulmonary vascular remodeling and production of superoxide anions.The measurement of PAP showed that the MCT group (37 ± 3 mmHg; n= 4) presented increased right ventricular systolic pressure, compared to the CTL group (20 ± 2 mmHg; n= 4). The MCT+CRV 50mg/Kg (24 ± 1 mmHg; n= 4) and MCT+SILD (21 ± 4 mmHg; n= 4) groups significantly attenuated the pressure. Regarding to index of right ventricular hypertrophy the MCT group (0,38± 0,02 g; n= 4) showed an elevated compared to the CTL group (0,23 ± 0,04 g; n= 4). The MCT+CRV 50mg/Kg (0,26 ± 0,02g; n= 4) and MCT+CRV 100mg/Kg (0,26 ± 0,05g; n= 4) groups significantly reduced the right ventricular hypertrophy. The vascular reactivity analysis showed that the contractions to phenylephrine (Phe) as well as vasodilation to acetylcholine (ACh) or sodium nitroprusside (SNP) were significantly reduced (Emax = 66 ± 5%; n= 6, Emax = 44 ± 8%; n= 6, or Emax = 78 ± 3%; n= 8, respectively) in the MCT group compared to CTL group. On the other hand, treatment with CRV (MCT+CRV 50 mg/kg or MCT+CRV 100 mg/kg) significantly improved contractions to Phe (Emax = 98 ± 9%; n= 6, or Emax= 88 ± 8%; n= 6, respectively) or vasodilations to ACh (Emax= 75 ± 8%; n= 7, or Emax = 130 ± 13%; n= 5, respectively). Nevertheless, no significant alterations were observed to SNP, excepting that vasodilation was improved in the MCT+CRV 50mg/kg group (Emax = 90 ± 2%; n= 8). Histological analysis of the pulmonary artery wall showed that the MCT (310 ± 5,2 %; n= 5) group presented thickening of the vessel wall, with a significant increase of smooth muscle cells when compared to the CTL (100 ± 5,2 %; n=5) group. The MCT+CRV 100mg/Kg (147 ± 10,5 %; n= 5) and MCT+SILD (94 ± 10,5 %; n= 5) groups attenuated the proliferation of smooth muscle cells. Regarding the analysis of oxidative stress in the tissues of the pulmonary arteries, it was observed that the MCT group (216 ± 22%; n= 5) presented a high percentage of fluorescence when compared to the CTL group (100 ± 6%; n= 5). The MCT+CRV 50mg/Kg (119 ± 8%; n= 5); MCT+CRV 100mg/Kg (68 ± 6%; n= 5) and MCT+SILD (96 ± 7%; n= 5) groups attenuated the oxidative stress. These results demonstrate that the model chosen for the induction of PH, monocrotaline, is effective in bringing the structural and functional alterations of the pulmonary artery, generating physiological alterations similar to that occurring in humans. In addition, the carvacrol has been shown to be a promising substance for the treatment of PH, since it attenuates pulmonary arterial pressure, right ventricular hypertrophy, pulmonary vascular remodeling, improves endothelial dysfunction, and reduces tissue oxidative stress.